2019
DOI: 10.32404/rean.v6i2.3323
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping of Morphological and Physiological Traits of Flag Leaf Related to Drought Tolerance in Barley

Abstract: Association mapping (AM) has proven to be a powerful approach for dissecting the genetic basis of complex traits. In this study, Quantitative Trait Loci (QTLs) controlling flag leaf characteristics under drought stress were detected in a set of 148 modern spring barley cultivars using AM analysis. Flag leaf length (FLL), flag leaf width (FLW), relative water content (RWC), chlorophyll content, and maximum quantum efficiency of PSII (Fv/Fm) which are important in photosynthetic rate, were evaluated under normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Most of the studies on lodging focused on plant height and stem chemical composition ( JSameri et al., 2009 ; Ren et al., 2013 ; Ren et al., 2014 ; Wehner et al., 2015 ; Gong et al., 2016 ; Wendt et al., 2016 ; Al-Abdallat et al., 2017 ; Bélanger et al., 2018 ; Hu et al., 2018 ; Pu et al., 2021 ), on heading date focused on the change of agronomic traits under drought stress and panicle traits in barley ( Pasam et al., 2012 ; Long et al., 2013 ; Alqudah et al., 2014 ; Gawenda et al., 2015 ; Mohammadi et al., 2015 ; Alqudah et al., 2016 ; Kristensen et al., 2016 ; Maurer et al., 2016 ; Alqudah et al., 2018 ; Jabbari et al., 2018 ; Abdel-Ghani et al., 2019 ; Jia et al., 2019 ; Ward et al., 2019 ; Jabbari et al., 2019 ; Moualeu-Ngangue et al., 2020 ), but few studies on QTL mapping of stem diameter of internode or node were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on lodging focused on plant height and stem chemical composition ( JSameri et al., 2009 ; Ren et al., 2013 ; Ren et al., 2014 ; Wehner et al., 2015 ; Gong et al., 2016 ; Wendt et al., 2016 ; Al-Abdallat et al., 2017 ; Bélanger et al., 2018 ; Hu et al., 2018 ; Pu et al., 2021 ), on heading date focused on the change of agronomic traits under drought stress and panicle traits in barley ( Pasam et al., 2012 ; Long et al., 2013 ; Alqudah et al., 2014 ; Gawenda et al., 2015 ; Mohammadi et al., 2015 ; Alqudah et al., 2016 ; Kristensen et al., 2016 ; Maurer et al., 2016 ; Alqudah et al., 2018 ; Jabbari et al., 2018 ; Abdel-Ghani et al., 2019 ; Jia et al., 2019 ; Ward et al., 2019 ; Jabbari et al., 2019 ; Moualeu-Ngangue et al., 2020 ), but few studies on QTL mapping of stem diameter of internode or node were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes with high adaptability to drought stress may serve as genetic resources to enhance drought stress tolerance (Liaqat et al, 2021). Selection for drought tolerance has focused extensively on agronomic and physiological traits, such as grain yield (Mora et al, 2016), biomass yield (Szira et al, 2008), root morphology (Hargreaves et al, 2008), relative water content (Szira et al, 2008), stomatal conductance (Munns et al, 2010), photosynthetic parameters (Gudys et al, 2018;Rapacz et al, 2019), chlorophyll fluorescence (Guo et al, 2007;Jabbari et al, 2019;Rapacz et al, 2019), osmotic adjustment (Teulat et al, 2001a), and hormone content (Gudys et al, 2018).…”
Section: Morpho-physiological Mechanisms Of Barley Drought Tolerancementioning
confidence: 99%
“…QTL mapping for barley drought tolerance was carried out using different biparental populations produced from crosses between barley cultivars (Fan et al, 2015; Teulat et al, 2002; Wójcik‐Jagła et al, 2013), between Hordeum vulgare and Hordeum spontaneum genotypes (Baum et al, 2003; Sayed et al, 2012; Talame et al, 2004) or between H. spontaneum genotypes (Chen et al, 2010). Besides, there have also been more recent genome wide association studies for drought tolerance of barley using different germplasm collections (Jabbari et al, 2019; Thabet et al, 2020; Wehner et al, 2015). In barley ‘Tadmor’ × Er/Apm mapping population, a genomic region around the EBmac0684 marker on chromosome 2 (2H) was found to be associated with drought tolerance provided by carbon isotope discrimination and osmotic adjustment (Teulat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%